The sea wolves - Cussler, Clive; Du Brul, Jack B (Cussler, Clive. Isaac Bell novels, 2022)
As New England swelters in the summer of 1914, Detective Isaac Bell is asked to investigate a cache of missing rifles -- only to discover something much more sinister involving a transistor radio set to summon German U-Boats.